An autologous platelet-rich plasma hydrogel compound restores left ventricular structure, function and ameliorates adverse remodeling in a minimally invasive large animal myocardial restoration model: A translational approach: Vu and Pal "Myocardial Repair: PRP, Hydrogel and Supplements". (March 2015) - Vu, Thang Duc; Pal, Shripad N.; Ti, Lian-Kah; Martinez, Eliana C.; Rufaihah, Abdul Jalil; Ling, Lieng H.; Lee, Chuen-Neng; Richards, Arthur Mark; Kofidis, Theo
Abstract: Aims: Cell-based myocardial restoration has not penetrated broad clinical practice yet due to poor cell retention and survival rates. In this study, we attempt a translational, large-scale restorative but minimally invasive approach in the pig, aiming at both structurally stabilizing the left ventricular (LV) wall and enhancing function following ischemic injury. Methods and results: A myocardial infarction (MI) was created by permanent ligation of left circumflex coronary artery through a small lateral thoracotomy. Thirty-six Yorkshire pigs were randomized to receive transthoracic intramyocardial injection into both infarct and border zone areas with different compounds: 1) Hyaluronic acid-based hydrogel; 2) autologous platelet-rich plasma (PRP); 3) ascorbic acid-enriched hydrogel (50 mg/L), combined with IV ibuprofen (25 mg/kg) and allopurinol (25 mg/kg) (cocktail group); 4) PRP and cocktail (full-compound); or 5) saline (control). The latter two groups received daily oral ibuprofen (25 mg/kg) for 7 days and allopurinol (25 mg/kg) for 30 days, postoperatively. Hemodynamic and echocardiographic studies were carried out at baseline, immediately after infarction and at end-point. Eight weeks after MI, the full-compound group had better LV fractional area change, ejection fraction and smaller LV dimensions than the control group. Also, dp/dtmax was significantly higher in the full-compound group when the heart rate increased from 100 bpm to 160bpm in stress tests. Blood vessel density was higher in the full-compound group, compared to the other treatment groups. Conclusions: A combination of PRP, anti-oxidant and anti-inflammatory factors with intramyocardial injection of hydrogel has the potential to structurally and functionally improve the injured heart muscle while attenuating adverse cardiac remodeling after acute myocardial infarction.